Mobil catalytic material number 41 modified magnetite nano‐composites for efficient extraction of non‐steroidal anti‐inflammatory drugs from tap water and urine samples. Issue 8 (14th June 2022) - Kumar, Sandeep; Bhogal, Shikha; Sharma, Promila; Rani, Susheela; Aulakh, Jatinder Singh; Malik, Ashok Kumar
Abstract: Magnetite modified mobil catalytic material number 41 (MCM‐41) nano‐composites have been synthesized for the effective determination and separation of non‐steroidal anti‐inflammatory drugs (diclofenac, ketoprofen, and mefenamic acid) using high‐performance liquid chromatography. The synthesized magnetite‐modified MCM‐41 nano‐composites were characterized by scanning electron microscopy coupled with energy dispersed spectrum, transmission electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, N2 adsorption‐desorption analysis, and vibratory sample magnetometer analysis. Magnetite modified MCM‐41 was further utilized in magnetic solid‐phase extraction to separate non‐steroidal anti‐inflammatory drugs from tap water and urine samples. The as‐prepared nano‐composites demonstrated a fast (5 min) and efficient (94.42%–102.42%) technique for the detection of non‐steroidal anti‐inflammatory drugs. The limit of detection and limit of quantification of the developed method were in the range of 0.08–0.14 and 0.26–0.46 ng/ml respectively.